Modelos de sobrevivência de longa-duração : uma abordagem unificada - Iritani, Mateus Rodrigues (2008)
In survival analysis some studies show a meaningful cure rate after treatment followup, so considering standard survival models can not be appropriate. In this work is extended the long-term survival model proposed by Chen, Ibrahim and Sinha (1999) via generating function of a real sequence introduced by Feller (1967). This new formulation is the uni_cation of the long-term survival models proposed by Rodrigues el al. (2008). Also, as in Rodrigues el al. (2008) it is shown that the long-term survival generating function satis_es the proportional hazard property if only if the number of competing causes related to the occurence of a event of interest follows a Poisson distribution. A real data set is considered to illustrate this approach.